Exploring alternatives to the hate crimes model. Perceptions of civil society organizations regarding the application of restorative justice for bias-motivated crimes - Mas Grau, Jordi (Contemporary justice review, 2023)
Most European countries have adopted the hate crimes paradigm in their criminal systems for combating bias-motivated violence. This model contributes to increasing public awareness about the unacceptability of violence committed against vulnerable groups, and the need to provide them with formal protection. However, the hate crime model has been challenged, under the auspices that the widespread failure of criminal punishment to act as a deterrent to crime calls into question the extent to which hate crimes legislation actually reduces violence towards a particular group. An alternative or complement to the punitive and individualistic approach of hate crimes that could ensure adequate reparation for criminal behavior is the implementation of restorative justice programs. In this article we present and discuss the results of the survey (n = 288) carried out in six European countries (Belgium, Bulgaria, Italy, the Netherlands, Poland and Spain) with the aim of gathering the knowledge, perceptions and practices regarding restorative justice of representatives of the main LGBT associations and other civil society organizations that fight against discrimination. The results obtained show that restorative justice is still an incipient jurisdictional paradigm that requires further consolidation if it is to constitute an alternative to the punitive model of hate crimes.